2008
DOI: 10.1007/s00439-008-0571-z
|View full text |Cite
|
Sign up to set email alerts
|

MMP-1 polymorphisms and the risk of idiopathic pulmonary fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a chronic and progressive fibrotic lung disorder of unknown etiology and unclear pathogenesis. Matrix metalloproteinase-1 (MMP-1) is strongly upregulated and may contribute to the abnormal remodeling that characterizes the disease. We conducted a case-control study of 130 IPF patients and 305 healthy controls to investigate associations between two polymorphisms of the MMP-1 gene promoter and IPF risk. First, using PCR-restriction fragment length polymorphism (PCR-RFLP) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 21 publications
1
49
0
2
Order By: Relevance
“…MMPs (49,50,53), neutrophil elastase (54,55), and proteinases of the coagulation cascade (56 -60) have all been implicated in the disease. Although the balance of the literature to date indicates a profibrotic action of these particular proteases, we have found that FAP, a serine protease in the DPP family, exerts a protective anti-fibrotic effect in the setting of lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…MMPs (49,50,53), neutrophil elastase (54,55), and proteinases of the coagulation cascade (56 -60) have all been implicated in the disease. Although the balance of the literature to date indicates a profibrotic action of these particular proteases, we have found that FAP, a serine protease in the DPP family, exerts a protective anti-fibrotic effect in the setting of lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…PCR products were digested with the respective restriction endonucleases (New England Biolabs, Inc., Ipswich, MA, USA), and the resulting fragments were separated on a 2.5% agarose gel containing 0.5 mg/mL ethidium bromide by electrophoresis at 100 V and visualized under UV light. Primer design was based on published sequences (Jurajda et al, 2002;Jin et al, 2005;Li et al, 2007;Checa et al, 2008;Kalousova et al, 2009;Daborg et al, 2010). The details of the primers, PCR conditions, restriction enzymes, and genotype configurations are shown in …”
Section: Selection and Genotyping Of Polymorphismsmentioning
confidence: 99%
“…A genetic polymorphism in the MMP1 promotor was linked to IPF in smoking individuals [62]. Rosas et al simultaneously analyzed forty-nine different serum markers and found five MMPs among the twelve proteins differentially expressed in serum from patients with IPF.…”
Section: Mmpsmentioning
confidence: 99%